Personality Traits and Work Performance of Teachers in Universities in China - Zhang, Xin; Zhang, Wenhao; Yu, Jiawen; Gao, Xinxiang (Environment-Behaviour Proceedings Journal, 2025)
This study aims to explore how the Big Five personality traits (BFPT) influence the work performance (WP) of teachers in universities and establish the mediating role of sense of belonging (SB) and used purposive sampling to survey 391 application-oriented university teachers in China and conducted analysis using PLS-SEM. The results showed that BFPT -Extraversion, Agreeableness, Neuroticism, and Openness were significantly positively correlated with teachers’ WP, while Conscientiousness had no significant relationship with performance. In addition, the SB showed a mediating effect in all the significant paths mentioned above. This study includes recommendations, limitations, and future research prospects.